Turnover of microbial biomass, plant residues and soil humic constituents under field conditions - McGill, W. B., author; Paul, Eldor A., author; International Atomic Energy Agency, publisher (Colorado State University. Libraries, 1977)
The effects of soil texture and climatic conditions on turnover rates of plant residues were measured under field conditions. Carbon-14- and 15N-labelled straw made it possible to follow degradation rates of the original substrate and of the soil organic constituents formed during the initial degradation process. Subsequent sampling measured the turnover of the active fraction. Carbon dating was used to measure the turnover rates of the more resistant fraction. Fractionation of the soil during the first two years showed greater accumulation of a condensed aromatic moiety (humic acid A) in the medium-textured Luvisolic soil and in the coarse-textured Dark Brown Chernozemic (Kastanozem). High clay grassland soils showed protection of aliphatic nitrogen from further humification. Much of the initial nitrogen and carbon mineralization of soil organic materials produced on decomposition of the straw came from the fulvic acids which contained a predominance of recently synthesized low molecular weight materials. Carbon and nitrogen incorporation into the > 0.2 μm fraction lagged behind incorporation into other fractions. Large quantities of immobilized carbon and nitrogen were contained in the > 0.2 μm fraction as well as in the 0.04 μm sedimentation fraction allowing these two fractions to act as sources of slowly released nitrogen. Residual humic acid carbon and nitrogen turnover was best estimated from carbon dating of the carbon after fractionation of the soil. The nitrogen turnover was calculated utilizing the C/N ratios of the fractions. Acid hydrolysis was found to be the simplest method of fractionation of large quantities of soil for carbon dating and for specific components. Na4P2O7 extraction followed by peptization and sediment analysis proved useful for measuring C and N transformations on a shorter term basis.
Keywords: fractionation; soil; C; N